PENGARUH PROGRAM KELOMPOK â€œAJIâ€ DALAM PENINGKATAN HARGA DIRI, ASERTIVITAS, DAN PENGETAHUAN MENGENAI NAPZA UNTUK PREVENSI PENYALAHGUNAAN NAPZA PADA REMAJA - Afiatin, Tina (Jurnal Psikologi, 2004)
A program to prevent NAPZA abuses by teenagers were designed to improve both NAPZA knowledge and interpersonal and personal competencies. This research was performed to test influences of the program of AJI group in preventing NAPZA abuses in adolescents having high risks toward NAPZA abuses. The research subjects were early teenagers studying at schools located in the Sleman Regency, Yogyakarta. The number of subjects was 200 people and they were grouped using random assignment into a 100-person experimental group and a 100-person control group. The tool used to collect data was Self- Esteem Scale (adaptations of Self-Esteem Inventory from Coopersmith), Assertiveness Scale (adaptations of The Ratus Assertiveness Schedule), Scale of NAPZA knowledge (Afiatin, 1999) and list of NAPZA abuse signs (Gordon, 1999). The analysis of data used Mixed Variance Analysis (Anava Mixed 1 path x 1 factor) in order to recognize differences in self esteem, assertiveness, and NAPZA knowledge in before, after and further actions of treatments. The Anava Mixed was also used to recognize differences in NAPZA abuse signs between the experimental group subjects and the control group subjects between before and six months after treatments. The research results showed that: (1) there was a difference in self esteem, assertiveness and NAPZA knowledge between teenagers involved in the program of AJI group and who involved in the NAPZA extension; self esteem, assertiveness and NAPZA knowledge in teenagers involved in the program of AJI group was better than who involved in the NAPZA extension; (2) there was a difference in NAPZA abuse signs between teenagers involved in the program of AJI group and who involved in the NAPZA extension; the teenagers involved in the program of AJI group had NAPZA abuse signs than who involved in the NAPZA extension. Implementations of the research results in the efforts of preventions of NAPZA abuses in the teenagers in schools still needed further discussions. Based on the research results and discussions, it could be concluded that the program of AJI group could become a model in preventions of NAPZA abuses in teenagers. Keywords: prevention â€“ NAPZA Abuses â€“ Program of â€œAjiâ€ Group.